2013
DOI: 10.1177/1079063213480817
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Measures of Sexual Maturity Preferences Differentiate Subtypes of Child Sexual Abusers

Abstract: To aid risk assessment, management, and treatment planning it is essential to assess child sexual abusers’ deviant sexual interests (DSI) and preferences (DSP) for sex with children. However, measurement of DSI/DSP is fraught with psychometric problems. In consequence, research interest has shifted to latency-based indirect measures as a measurement approach to complement self-report and physiological assessment. Utilizing the Explicit and Implicit Sexual Interest Profile (EISIP)—a multimethod approach consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 61 publications
2
42
1
2
Order By: Relevance
“…This has important implications for applied forensic contexts: First of all, if scored properly (i.e., difference scores), VT outperforms IATs in terms of known-groups discrimination. This finding is corroborated in all available studies comparing both VT and IAT paradigms in the same sample (Babchishin et al, 2014;Banse, Schmidt, & Clarbour, 2010;Schmidt, Gykiere, et al, 2014;Schmidt et al, 2013, Schmidt, Bonus, & Banse, 2010.…”
Section: Variability Of Viewing Time Validitysupporting
confidence: 74%
See 2 more Smart Citations
“…This has important implications for applied forensic contexts: First of all, if scored properly (i.e., difference scores), VT outperforms IATs in terms of known-groups discrimination. This finding is corroborated in all available studies comparing both VT and IAT paradigms in the same sample (Babchishin et al, 2014;Banse, Schmidt, & Clarbour, 2010;Schmidt, Gykiere, et al, 2014;Schmidt et al, 2013, Schmidt, Bonus, & Banse, 2010.…”
Section: Variability Of Viewing Time Validitysupporting
confidence: 74%
“…Additionally, VT difference measures of one stimulus category over another stimulus category inherently control for potential influences of general processing speed as baseline response latency is canceled out of the final score. Accordingly, general processing speed was not associated with relative VT measures of sexual interest in children (r = -.07; Schmidt, Gykiere et al, 2014). Furthermore, when the highest mean category latency for male or female adult stimuli is subtracted from the highest mean category latency for male or female child stimuli the resulting maximized pedophilic differential score also controls for respondents' sexual gender preferences (i.e., sexual orientation).…”
Section: Scoring Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, such a combination of conceptually diverse measures has been successfully applied for the assessment of pedophilic sexual preferences for children as this multimethod approach reduces measurement error due to the diagnostic convergence principle Schmidt, Gykiere, Vanhoeck, Mann, & Banse, 2014;Schmidt, Mokros, & Banse, 2013). Additionally, although being related to self-report assessments indirect measures usually predict behavioral variation not accounted for by explicit self-reports (Nosek et al, 2011; specifically for sexual interests see Banse et al, 2010;Schmidt et al, 2013).…”
Section: Present Researchmentioning
confidence: 99%
“…Finally, individuals who show high PSV but have never committed any sexual crime -and never will -would not be included in the sample, biasing our measures towards overestimating the relation between PSV and violent sexual offending. Consequently, in light of a lack of an ultimate and observable criterion for PSV, the best strategy to validate new measures of sexual interest is to use a multi-method approach and to rely on the convergence of conceptually different indicators of the construct in Indirect Measures of Preference For Sexual Violence 11 question (e.g., Banse et al, 2010;Schmidt, et al, 2014;Schmidt, Mokros, & Banse, 2013) as operationalized by self-identified BDSM-affiliates that openly acknowledge their PSV in an anonymous context where social desirability concerns are minimized.…”
Section: Present Researchmentioning
confidence: 99%